JC virus-associated nephropathy in a renal transplant recipient and comparative analysis of previous cases - (:unkn) unknown (WILEY-BLACKWELL PUBLISHING, INC, 2011)
P>We report JC virus (JCV)-associated nephropathy in a renal allograft recipient and summarize the clinical and laboratory data of the 8 previous cases. A 28-year-old male renal allograft recipient received a preemptive transplant from his father. Six months later, a kidney biopsy was performed because of deterioration of allograft function. Biopsy revealed tubulointerstitial mononuclear infiltrates with normal glomeruli; on hematoxylin and eosin staining, basophilic nuclear inclusions were seen in the nucleus of tubular cells. Urinary cytology failed to demonstrate decoy cells, but polymerase chain reaction of a urinary sample was positive for JCV 3.15 x 1010 copies/mL. Additionally, polyomavirus (SV40) immunohistochemical staining was performed and was positive in the enlarged nuclei of tubular epithelial cells in the kidney biopsy sample. After the diagnosis of polyomavirus-associated nephropathy (PVAN) was confirmed by kidney biopsy, immunosuppressive agents were reduced. Intravenous immunoglobulin was administered 5 times at a dose of 500 mg/kg every other 3 weeks. Two months after diagnosis, the serum creatinine became stable and urinary viral load of JCV was decreased. Because viruria was still present, tacrolimus was converted to sirolimus. Four months after immunosuppressive agent conversion from tacrolimus to sirolimus, the viruria had disappeared. Review of the literature and our case demonstrates that male gender, previous acute rejection episode, low incidence of JCV viremia, PVAN pattern B histology, and reducing immunosuppression are the diagnostic touchstones for PVAN due to JCV.
Keywords: JC virus; polyoma virus nephropathy; renal transplantation; ALLOGRAFT NEPHROPATHY; BK; REPLICATION